Pomegranate: A Source of Multifunctional Bioactive Compounds Potentially Beneficial in Alzheimer's Disease - Lidia Ciccone; Susanna Nencetti; Armando Rossello; Elisabetta Orlandini (MDPI AG, 2023)
Pomegranate fruit (PF) is a fruit rich in nutraceuticals. Nonedible parts of the fruit, especially peels, contain high amounts of bioactive components that have been largely used in traditional medicine, such as the Chinese, Unani, and Ayurvedic ones, for treating several diseases. Polyphenols such as anthocyanins, tannins, flavonoids, phenolic acids, and lignans are the major bioactive molecules present in PF. Therefore, PF is considered a source of natural multifunctional agents that exert simultaneously antioxidant, anti-inflammatory, antitumor, antidiabetic, cardiovascular, and neuroprotective activities. Recently, several studies have reported that the nutraceuticals contained in PF (seed, peel, and juice) have a potential beneficial role in Alzheimer's disease (AD). Research suggests that the neuroprotective effect of PF is mostly due to its potent antioxidant and anti-inflammatory activities which contribute to attenuate the neuroinflammation associated with AD. Despite the numerous works conducted on PF, to date the mechanism by which PF acts in combatting AD is not completely known. Here, we summarize all the recent findings (in vitro and in vivo studies) related to the positive effects that PF and its bioactive components can have in the neurodegeneration processes occurring during AD. Moreover, considering the high biotransformation characteristics of the nutraceuticals present in PF, we propose to consider the chemical structure of its active metabolites as a source of inspiration to design new molecules with the same beneficial effects but less prone to be affected by the metabolic degradation process.